Pengaruh Good Corporate Governance Terhadap Manajemen Laba Dengan Financial Distress - Al Awwaliyah, Nur Maisunatul Aflachiyah; Susyanti, Jeni; Asiyah, Siti (Jayapangus Press, 2024)
The aim of this research is to test the influence of the size of the board of directors (x1), independent commissioners (x2), audit committee (x3), managerial ownership (x4) on earnings management (Y) and to test the mediating effect of the influence of the size of the board of directors (x1), independent commissioner (x2), audit committee (x3), managerial ownership (x4) through financial distress (Z) to earnings management (Y). The type of research used in this research is quantitative research, used to test data that uses numbers as test material which are measured using statistics as a test tool related to the research problem to produce a conclusion. The data in this study used a purposive sampling technique, including companies that were not listed on the IDX consecutively from 2018-2022, companies that did not report financial reports during the 2018-2022 period, companies that did not distribute dividends in the last 5 years, companies who do not make a profit.